Kemampuan Mahasiswa dalam Mengkonstruksi Paragraf di Era Digital - Aryandi Sudika; mantasiah R.; Juanda Juanda (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2025)
Writing skills play an important role in supporting academic and professional communication, especially in the technology-dominated digital era. This study uses a qualitative approach to analyse students' ability to structure paragraphs, discover their strengths and weaknesses, and explore the influence of digital technology in learning to write. The findings show that students face challenges in constructing topic sentences, developing ideas, and stringing together relevant supporting sentences. Digital media, such as social media and blended learning, help them understand different types of writing, but the quality of the paragraphs produced has not met academic standards. The use of digital technologies, including platforms such as Facebook, improved students' motivation and writing performance and helped distinguish between informal and formal writing. The blended technology-based learning approach is effective in gradually improving writing skills, although further strategies are needed to ensure the quality of writing meets academic standards in the digital era. This research makes a novel contribution by presenting an innovative approach that leverages specific digital platforms, such as Facebook, supplemented with metadata to analyse its impact on the development of academic writing skills. Keywords: paragraph writing skills; learning; technology Abstrak Keterampilan menulis memiliki peran penting dalam mendukung komunikasi akademik dan profesional, terutama di era digital yang didominasi teknologi. Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis kemampuan mahasiswa dalam menyusun paragraf, menemukan kelebihan dan kelemahan mereka, serta mengeksplorasi pengaruh teknologi digital dalam pembelajaran menulis. Temuan menunjukkan bahwa mahasiswa menghadapi tantangan dalam menyusun kalimat topik, mengembangkan ide, dan merangkai kalimat pendukung yang relevan. Media digital, seperti media sosial dan pembelajaran campuran, membantu mereka memahami berbagai jenis tulisan, tetapi kualitas paragraf yang dihasilkan belum memenuhi standar akademik. Penggunaan teknologi digital, termasuk platform seperti Facebook, meningkatkan motivasi dan performa menulis mahasiswa serta membantu membedakan tulisan informal dan formal. Pendekatan pembelajaran berbasis teknologi campuran efektif dalam meningkatkan keterampilan menulis secara bertahap, meskipun diperlukan strategi lebih lanjut untuk memastikan kualitas tulisan memenuhi standar akademik di era digital. Penelitian ini memberikan kontribusi baru dengan menghadirkan pendekatan inovatif yang memanfaatkan platform digital tertentu, seperti Facebook, yang dilengkapi dengan metadata untuk menganalisis dampaknya terhadap pengembangan keterampilan menulis akademik. Katakunci: keterampilan menulis paragraf; pembelajaran; teknologi _______